PERANCANGAN DAN VALIDASI DESAIN ALAT PENUKAR KALOR TIPE SHELL AND TUBE MENGGUNAKAN COMPUTATIONAL FLUID DYNAMICS - Eko Kiswoyo; Anwar Ilmar Ramadhan (Dinamika : Jurnal Ilmiah Teknik Mesin, 2017)
In this study will be analyzed on a heat exchanger shell and tube type by using CFD (Computational Fluids Dynamic) and analytic calculations. The results of the analysis will be compared later searched the differences and similarities that can be seen the effect that makes a difference or similarity of the analysis results. Analysis using Computational Fluid Dynamics (CFD) includes the manufacture of the model, determining boundary condition, the manufacture of mesh, material data input, then the iteration process. After the iterative process, we will get the results in a visual form by using a color scale. Analysis manual calculation performed after all the data is collected and then put into the calculation formula. The results of both analyzes are the difference in temperature that comes out of the shell of 1.84 0F. The difference is due to the difference in the CFD analysis results visually using a color scale that is not an exact figure. As for the manual analysis calculations using exact numbers, so there are differences in the results. Nevertheless, these differences are relatively small but in terms of efficiency calculations using CFD program is better than the manual calculation.Keywords: planning, design, heat exchanger, CFD